Batman : off-world - Aaron, Jason (DC Comics, 2025)
"Batman, new to the crime-fighting lifestyle, must face off against this interstellar threat. During this battle Batman thinks "what other threats could be looming in the deep reaches of space"? This question sends the Dark Knight on a quest through the deep reaches of space, facing off against cosmic villains. Throughout this crusade he'll team up with deadly mercenaries and truly learn what it means to be a hero of the universe in a unique and brutal tale."-- Provided by publisher.